2009
DOI: 10.1523/jneurosci.5251-08.2009
|View full text |Cite
|
Sign up to set email alerts
|

Splice-Variant- and Stage-Specific RNA Editing of theDrosophilaGABA Receptor Modulates Agonist Potency

Abstract: The molecular diversity of many gene products functioning in the nervous system is enhanced by alternative splicing and adenosine-toinosine editing of pre-mRNA. Using RDL, a Drosophila melanogaster GABA-gated ion channel, we examined the functional impact of RNA editing at several sites along with alternative splicing of more than one exon. We show that alternative splicing and RNA editing have a combined influence on the potency of the neurotransmitter GABA, and the editing isoforms detected in vivo span the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
77
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(82 citation statements)
references
References 37 publications
5
77
0
Order By: Relevance
“…Met 360 is one of four RNA-editing locations in Rdl. Editing to Val occurs in 10% of adult head Rdl BD transcripts, where Rdl BD is the most common splice isoform of four alternately spliced transcripts (26).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Met 360 is one of four RNA-editing locations in Rdl. Editing to Val occurs in 10% of adult head Rdl BD transcripts, where Rdl BD is the most common splice isoform of four alternately spliced transcripts (26).…”
Section: Resultsmentioning
confidence: 99%
“…Forty-five individual clones were sequenced to identify whether both copies of Rdl were expressed and if the two derived nonsynonomous variants were found in the same copy. This tissue and life stage were chosen to determine whether Met 360 to Val RNA editing still occurred correctly in Ile 360 mutants (26).…”
Section: Resultsmentioning
confidence: 99%
“…Edited adenosines exhibiting differential developmental regulation may even be found within the same transcript (23,24), yet how this is achieved remains unknown. Previous data has shown that dAdar transcription is low during the larval stages and rapidly peaks at the late pupal and adult stages (25).…”
Section: Stringent Reduction Of Dadar Expression Reveals Differentialmentioning
confidence: 99%
“…Secondly, recent studies have shown that epistatic interactions between editing sites in both the shaker potassium channel and the rdl GABA A receptor regulate protein function. 18,19 The fact that we were unable to fully recapitulate endogenous editing levels (leading to the generation of edited isoforms that may normally be very rare in vivo) suggests that the true adult-stage requirement for A-to-I editing is likely to be higher than our rescue data indicates, particularly when considering our transgenic RNAi data that shows a requirement for dADAR activity in nonneuronal tissues.…”
Section: Future Directionsmentioning
confidence: 95%
“…This conclusion is parsimonious with previous data showing that dAdar mRNA levels peak at later stages of development, 9 as does editing of many dADAR targets. [18][19][20] However, given the complexity of dADAR regulation, the diversity of target adenosines, and the potential for pleiotropic effects on development, gene regulation and neuronal firing properties in the absence of A-to-I editing, an absolutist position seems inappropriate. Although we failed to observe any negative epistasis between dAdar and a variety of RNAi components, interactions between these two pathways may still be physiologically relevant and open to natural selection.…”
Section: Future Directionsmentioning
confidence: 99%